(untitled) (Global Journal of Management and Business Research, 2014)
This paper explains the historical development of marketing education and professional practice in Nigeria, it considers the marketing problems and advanced recommendations towards solving the numerous challenges. Emphasis was on the marketing curricular in Nigeria tertiary institutions. Also the important issue of the relationship between the marketing education and the marketing professional practice was considered. The onus of professionalism and success is moving from the professional institutes to the individual marketers. Here lies the success of marketing education in Nigeria, as qualified marketers will be practicing their art at a consistently high level, or they will bring the professional institute into disrepute. The focus of marketing is changing from brand to people and service which coupled with the shift from a manufacturing to a service economy means that much classical marketing theory is becoming if not redundant but less important.